Copy number variation in exportin-4 (XPO4) gene and its association with histological severity of non-alcoholic fatty liver disease - Zain, Shamsul Mohd; Mohamed, Zahurin; Pirmohamed, Munir; Tan, Hwa Li; Alshawsh, Mohammed Abdullah; Mahadeva, Sanjiv; Chan, Wah-Kheong; Mustapha, Nik Raihan Nik; Mohamed, Rosmawati (Scientific reports, 2015)
A recent genome-wide copy number (CNV) scan identified a 13q12.11 duplication in the exportin-4 ( XPO4 ) gene to be associated with non-alcoholic steatohepatitis (NASH). We sought to confirm the finding in a larger cohort and to assess the serum XPO4 pattern in a broad spectrum of non-alcoholic fatty liver disease (NAFLD) cases. We analysed 249 NAFLD patients and 232 matched controls using TaqMan assay and serum XPO4 was measured. Copy number distribution was as follows: copy number neutral (NAFLD: 53.8%, controls: 68.6%), copy number losses (NAFLD: 13.3%, controls: 12.9%), copy number gains (NAFLD: 32.9%, controls: 18.5%). CNV gain was significantly associated with a greater risk of NAFLD (adjusted OR 2.22, 95% CI 1.42–3.46, P = 0.0004) and NASH (adjusted OR 2.33, 95% CI 1.47–3.68, P = 0.0003). Interestingly, subjects carrying extra copy number showed significantly higher serum ALT and triglyceride (P < 0.05). Serum XPO4 levels progressively declined (P = 0.043) from controls (24.6 ng/mL) to simple steatosis (20.8 ng/mL) to NASH (13.8 ng/mL). In conclusion, XPO4 CNV duplication was associated with histological severity of NAFLD and accompanied by changes in serum XPO4 levels providing insights into NAFLD pathogenesis and has the potential for biomarker development.